Comparison of healthcare quality for uninsured and underinsured children through community health centres in Canada and the USA: a scoping review protocol - Eyal Cohen; Shazeen Suleman; Sabine Calleja; Puneet Kaur Parmar (BMJ Open)
Introduction Children and youth who are uninsured or underinsured in Canada and the USA have limited options where they can receive healthcare. In both countries, community health centres (CHCs) have been established as a solution to provide quality care to children without adequate insurance, including those who are newcomers or refugees. However, little is known about how well these models deliver paediatric care. Cross-country analysis provides an important viewpoint to identify areas of success and growth. The purpose of this scoping review is to compare quality of care for uninsured and underinsured children through CHCs in the USA and Canada.Methods This scoping review follows the methodological guidelines from the Joanna Briggs Institute Evidence synthesis. The protocol has been registered with the Open Science Framework Registries and can be accessed online. A search will be conducted in electronic databases of peer-reviewed literature (Ovid MEDLINE ALL, CINAHL Complete via EbscoHost, Scopus; Health Business Elite via EbscoHost and Sociological Abstracts via ProQuest) as well as the grey literature. Two reviewers will review all titles and abstracts for inclusion in full-text review. Studies that meet inclusion criteria will be included in full-text review. Data will be extracted into Covidence, using the Donabedian model as a conceptual framework. Findings will be synthesised in a narrative format.Ethics and dissemination As this study only uses publicly available data, ethics approval is not required. Findings will be shared at national and international conferences and published in a peer-reviewed journal. In addition, findings will be prepared into a policy brief or white paper to be shared with relevant policy stakeholders to advocate for a better model of care for marginalised children and youth.